Theoretical Justification of Structure and Development of Capsule Technology with Cerebroprotective Activity - Oleh S. Shpychak (Journal of Global Pharma Technology, 2020)
Treatment of brain remains an urgent problem in the health system in Ukraine, due to the wide prevalence of the most common as a result of this disease causes cerebrovascular diseases, including atherosclerosis and hypertension, leading to a narrowing of the blood vessels of the brain and decreased cerebral blood flow. An alternative method of treatment of cerebrovascular diseases (CVD) it is expected pharmacological effect, which is achieved through use in medicines herbal drug that exhibits antyarytmichal, sedative, tranquilizing, antispasmodic, antiseptic hypotensive effects. According to literature data types such therapeutic activity black horehound grass, the grass dead-nettle herb wormwood and compatible whose presence leads to a potentiation of pharmacological action due to the fact that the components of the content biologically active substances (BAS) show a complex impact on different parts of body systems and increase reliability and predictable therapeutic effect. This complex of action reduces the possibility of side effects of display. The aim of this work is the theoretical basis structure and development of technology for rational drug cerebroprotective action in the form of hard gelatin capsules based on dry extracts medical plant material (MPM), namely black horehound grass, herb nettle deaf, sage herb. On the basis of experimental studies, we have proved the composition of masses for encapsulation of drug in the form of hard gelatin capsules number 0. Composition per capsule: a mixture of dry extracts MPM-400 mg; aerosol-50 mg; lactose monohydrate -50 mg. The weight of the contents of the capsule-500 mg. Keywords: Dry extracts, Development composition and technology, Gelatin capsules, Cerebroprotective activity.